Tunable, reconfigurable, and programmable acoustic metasurfaces: A review - Zabihi, Ali; Ellouzi, Chadi; Shen, Chen (Frontiers in Materials, 2023)
The advent of acoustic metasurfaces (AMs), which are the two-dimensional equivalent of metamaterials, has opened up new possibilities in wave manipulation using acoustically thin structures. Through the interaction between the acoustic waves and subwavelength scatters, AMs exhibit versatile capabilities to control acoustic wave propagation such as steering, focusing, and absorption. In recent years, this vibrant field has extended to the regime of tunable, reconfigurable, and programmable control to further expand the capacity of AMs. This paper reviews the recent development of AMs and summarizes the fundamental approaches to achieve tunable control, namely mechanical tuning, active control, and the use of field-responsive materials. An overview of fundamental concepts in each category is first presented, followed by the details on their demonstration and performance. The review concludes with an outlook on the future directions in this exciting field.